(untitled) (Research, Society and Development, 2021)
Objective: To understand the confluences of the theory of “living work in the act” by Emerson Merhy and the process of permanent health education. Methodology: Theoretical reflection based on the concepts of the theory of “living work in the act” by Emerson Merhy in discussion with the National Policy of Permanent Education. Results: The liveliness of the work originates from the activity of the worker, in his exact moment of creation. In the field of Permanent Education, health work is centered on living work permanently, since it operates through the use of action technologies centered on relationships. Permanent Health Education presents itself as an effective management tool, being able to work with the realities and singularities of users, workers and health services, through meaningful learning. Final considerations: The confluences of Emerson Merhy’s theory of “live work in the act” and the National Policy on Permanent Education bring implications for the pedagogical and healthcare practice in health, as it allows to work a new perspective during the collective reflection of the work process, in addition to assisting in the implementation of Permanent Education in health services.